2020
DOI: 10.1101/2020.04.06.028316
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Extraction-free COVID-19 (SARS-CoV-2) diagnosis by RT-PCR to increase capacity for national testing programmes during a pandemic

Abstract: Severe Acute Respiratory Syndrome coronavirus 2 (SARS-CoV-2) causes Coronavirus disease 2019 (COVID-19), a respiratory tract infection. The standard molecular diagnostic test is a multistep process involving viral RNA extraction and real-time quantitative reverse transcriptase PCR (qRT-PCR). Laboratories across the globe face constraints on equipment and reagents during the COVID-19 pandemic. We have developed a simplified qRT-PCR assay that removes the need for an RNA extraction process and can be run on a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
85
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(90 citation statements)
references
References 2 publications
4
85
0
1
Order By: Relevance
“…Additionally, they found that direct sample addition in VTM without heating to the TaqMan Fast Virus 1-step Master Mix (Thermo Fisher) RT-qPCR reaction allowed detection 3.77 cycles earlier than the same test performed with RNA purified using the EZ1 Qiagen kit. Overall, their test using direct, unheated sample had 98.8% diagnostic accuracy when compared to cartridge-based RNA purification and RT-qPCR using the Panther Fusion system (Grant et al 2020). Intermediate inactivation temperatures seem to perform worse than high heat or no heating at all.…”
Section: Rtmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, they found that direct sample addition in VTM without heating to the TaqMan Fast Virus 1-step Master Mix (Thermo Fisher) RT-qPCR reaction allowed detection 3.77 cycles earlier than the same test performed with RNA purified using the EZ1 Qiagen kit. Overall, their test using direct, unheated sample had 98.8% diagnostic accuracy when compared to cartridge-based RNA purification and RT-qPCR using the Panther Fusion system (Grant et al 2020). Intermediate inactivation temperatures seem to perform worse than high heat or no heating at all.…”
Section: Rtmentioning
confidence: 99%
“…Another group reported that directly added samples were detected 3.5 cycles later than RNA isolated using the MagNA Pure kit (Roche), but heating the sample at 95°C for 5 minutes before direct-to-test addition resulted in detection only one cycle later, with 97.4% accuracy compared to tests using purified RNA (Fomsgaard and Rosenstierne 2020). However, Grant et al found the opposite -heating direct-to-test samples in VTM at 95°C for 10 minutes delayed detection of viral RNA compared to directly added samples not heated prior to amplification (Grant et al 2020). Additionally, they found that direct sample addition in VTM without heating to the TaqMan Fast Virus 1-step Master Mix (Thermo Fisher) RT-qPCR reaction allowed detection 3.77 cycles earlier than the same test performed with RNA purified using the EZ1 Qiagen kit.…”
Section: Rtmentioning
confidence: 99%
“…The CCC test was validated against the N gene assay developed by the reference laboratory (Health Services Laboratories, HSL) [6]. The N gene assay is a high throughput RT-PCR assay that runs on the Hologic Panther Fusion platform using the Open Access function which allows the use of custom primers and probe targeting the nucleocapsid (N) gene of SARS-…”
Section: N Gene Assaymentioning
confidence: 99%
“…Due to the unprecedented high demand in SARS-CoV-2 testing required to identify and isolate infected individuals, many laboratories are now facing shortages in reagents and consumables required for nucleic acid (NA) extraction. This has led us to investigate alternative sample processing methods that would remove the requirements for NA extraction 4,5,6,7 and allow rapid diagnosis.…”
Section: Introductionmentioning
confidence: 99%